Impact of LMS-mediated readiness assurance testing on performance in pharmacy calculations - Edward C. Bell (Springer, 2022)
Abstract Objective Readiness assurance testing has enjoyed increased use as a tool for the delivery and reinforcement of pharmacy concepts. This study was conducted to determine the influence of the readiness assurance test (RAT) on major examination outcomes in pharmacy calculations. Methods The Blackboard Learning Management System was identified as an efficient platform for RAT implementation. The outcomes of three consecutive offerings of pharmacy calculations were compared. Cohorts 1 and 2 were exposed to recitation and standard assessments in lecture and laboratory sessions. Cohort 3 was additionally administered weekly individual (IRAT) and team (TRAT) readiness assurance tests for concept areas. All cohorts were exposed to a common comprehensive final exam. Results Significant differences were observed in major lecture exam scores among cohorts. Cohort 3's mean final exam score was significantly greater than that of Cohort 1, which received the most conventional method of subject delivery. Students feedback was generally positive regarding use of RAT. Conclusions Use of RAT assessment was positively associated with final exam score outcomes in pharmacy calculations, including a positive shift in final exam score distribution in Cohort 3. Use of RAT promotes increased student exposure to conceptual material and instruction in pharmacy calculations.